Inner bark vs sapwood is the main driver of nitrogen and phosphorus allocation in stems and roots across three tropical woody plant communities - Rosell, Julieta A.; Marcati, Carmen R. [UNESP]; Olson, Mark E.; Lagunes, Xanath; Vergilio, Paula C. B. [UNESP]; Jiménez-Vera, Cipatli; Campo, Julio (Wiley, 2023)
Nutrient allocation is central to understanding plant ecological strategies and forest roles in biogeochemical cycles. Thought to be mainly driven by environmental conditions, nutrient allocation to woody organs, especially to living tissues, is poorly understood. To examine the role of differences in living tissues (sapwood, SW, vs inner bark, IB), organs, ecological strategies, and environmental conditions in driving nutrient allocation and scaling in woody plants, we quantified nitrogen and phosphorus in main stems and coarse roots of 45 species from three tropical ecosystems with contrasting precipitation, fire regime, and soil nutrients. Nutrient concentration variation was mostly explained by differences between IB and SW, followed by differences between species and, in the case of phosphorus, soil nutrient availability. IB nutrient concentrations were four times those of SW, with root tissues having slightly higher concentrations than stem tissues. Scaling between IB and SW, and between stems and roots, was generally isometric. In cross-sections, IB contributed half of total nutrients in roots and a third in stems. Our results highlight the important role of IB and SW for nutrient storage, the coordination in nutrient allocation across tissues and organs, and the need to differentiate between IB and SW to understand plant nutrient allocation.
Keywords: allometry; bark; root; sapwood; savanna; secondary phloem; tropical dry forest; tropical rainforest